PENGARUH PELATIHAN KERJA DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN BIREUEN - Isnaniah, Isnaniah; Zurlina, Zurlina; Muliyanti, Muliyanti (JURNAL KEBANGSAAN, 2023)
The study aims to analyze the influence of job training and work motivation on employee work productivity. With a study at the Manpower and Transmigration Office of Bireuen Regency. On a sample of 41 people. Applying associative research and data analysis techniques through multiple linear regression. The results found that; (1) Employee work productivity is significantly influenced by the existence of job training, (2) And work motivation factors have a real effect on employee work productivity, and (3) Simultaneously both factors, namely job training and motivation on employee work productivity at the Manpower and Transmigration Office of Bireuen Regency with a contribution of 33.6%.